Gentrificación y la nueva economía urbana en Barrio Logan: el Chicano Park como espacio público, resistencia cultural y contestación política (2009)
The article proposes a reflection on the dynamics of a nonprofit organization and the implementation area of a cultural project in Barrio Logan, San Diego (California) by means of using a multi-sited ethnography. Parting from the particular art and public space concepts that guide the cultural policies, this study redefines the neighborhood and its identity emblemas spaces for cultural resistance and political protestation to reveal a unique logic in comparison with the formation of other public spaces. Finally, in order to evaluate the project, the organization’s cultural project objectives are analyzed from the stand point of this redefinition.